Design of Automated Student Permission System using RFID and NodeMCU - BVR Gowri; S.S. Kiran; K. Gurucharan; Mouli Sai; A. Aswini; A. Venkatesh (International Journal of Mechanical Dynamics and Systems Analysis, 2023)
Automated Student Permission System is a system that can be used to automate the process of monitoring students attendance and granting permission to students to leave college early. The system works by having a sign-out sheet placed at the college's entrance that students can access using their college ID. When a student wants to leave the college early, they log in to the electronic sign-out sheet using their college ID. The authorities can either approve or deny the request based on the information provided by the student. This system can replace the traditional paper-based process of granting permission, making it more efficient and cost-effective. It eliminates the need for manual entry and reduces the risk of errors. Furthermore, the system provides a record of all sign-out requests for auditing purposes. A RFID transponder has been implanted in every classroom, lab, library, staff room, etc. through which we will be able to locate students and staff members. There will be a website where students, teachers, and parents may check a student's attendance status and current whereabouts on campus.
Keywords: Automated; NodeMCU; OTA; RFID; Wi-Fi connectivity